Comparative analysis, potential benefits, and safety of milk from five commercially milk-producing mammals - Maryam, Maqsood; Manzoor, Asia; Butt, Zil-e-Huma (Archives of Veterinary Science, 2023)
Milk production is a key feature of the Mammalia class. This study summarizes the characteristics of milk produced by the main dairy industry mammals: cows, buffalo, goats, sheep, and camels. The study compares their physical and chemical constituents, therapeutic benefits, and allergenicity and safety. The optimal milk for different situations can be identified using nutritional, medicinal, and safety studies. Cow milk is the most widely produced globally, accounting for more than eighty percent of the milk produced. Buffalo and sheep milk contain significantly more lactose than cow and goat milk. Bovine and bison milk have the highest cholesterol concentration. Goat milk has a higher fat content, while camel milk has fewer adverse effects. Consumption of cow or buffalo milk may induce minor allergic reactions; however, milk can also ease certain allergy problems. Sheep milk can benefit those with eczema and asthma. This research can help achieve a balanced utilization of varied milk varieties. The study aids consumers in choosing the right milk by investigating and comparing their commercial viability to cellular milk and other types of commercially accessible milk. In conclusion, the study highlights the advantages and disadvantages of different types of milk produced by the main dairy industry mammals. The choice of milk can depend on various factors such as nutritional content, allergenicity, and safety concerns. This research can help consumers make an informed choice regarding the optimal milk for different situations, which can aid in achieving a balanced utilization of varied milk varieties.